Ecological Embeddedness - Whiteman, Gail; Cooper, William H. (Academy of Management Journal, 2000)
The construct of social embeddedness has helped explain some of the ways in which individuals and organizations form and sustain alliances. We introduce the construct of ecological embeddedness, or the extent to which a manager is rooted in the land. Ecological embeddedness is illustrated by an ethnographic study of a Cree tallyman, or beaver trapper, in James Bay, northern Quebec. To be ecologically embedded as a manager is to personally identify with the land, to adhere to beliefs of ecological respect, reciprocity, and caretaking, to actively gather ecological information, and to be physically located in the ecosystem. We conclude by drawing some implications for sustainability.